Effect of Temperature on the Chemical Composition and Physicochemical Properties of Diester Aviation Lubrication Oil - Ting Yao; Na Zhang; Jianqiang Hu; Xiaoxiao Liao; Yongli Shen; Zhuoting Gan (International Journal of Chemical Engineering)
High temperature is the main factor responsible for degrading the lubrication and antiwear properties of aero-lubricating oils. Accordingly, this study assessed the effects of thermal treatment of diester aviation lubricating oil and the associated mechanism. Fourier-transform infrared spectroscopy and gas chromatography/mass spectrometry analyses showed that low-molecular-weight compounds, such as monoesters, diesters, alcohols, and olefins, were the primary degradation products. An assessment of the degradation mechanism of bis(2-ethylhexyl)decanedioate showed that pyrolysis, resulting in the cleavage of β-C–H and C–C bonds, was the main process involved. Additional investigation using advanced polymer chromatography showed that the molecular weights of oil samples changed slightly at high temperatures, while the viscosity and viscosity-temperature index values were relatively stable. High-pressure differential scanning calorimetry established that the thermal oxidation stability of these oils decreased above 250°C. Finally, variations in the chemical compositions of the oil samples were found to be highly correlated with changes in physicochemical properties during thermal processing, with the formation of low-molecular-weight polar compounds greatly increasing the acid numbers of the oils.